Knowledge production in health social work: an analysis of doctoral dissertations in Sweden. - Svärd, Veronica; Sernbo, Elisabet; Matérne, Marie (Social Work Education, 2025)
Health social work is often described as a blurred profession, as a work area based on an interdisciplinary field of science with an unclear knowledge foundation of its own. This study describes and analyses the knowledge production in Swedish doctoral dissertations in health social work, authored by social workers, from 2008 to 2019, and focuses on the differences between dissertations published by faculties of health and those in the social sciences. Descriptive statistical and content analysis was carried out on the 52 dissertations identified. Dissertations in the health sciences were often about specific patient groups within adult somatic care. They predominantly used mixed methods and psychological and psychosocial theories and models. Dissertations in the social sciences more often concerned adults in psychiatric or addiction care and the organization of social work. A majority used qualitative research methods, organization and profession theories, as well as interactionist and critical theories. The differences are discussed as being associated with different research ideals and traditions in the scientific disciplines. The findings raise questions about the core components of health social work and how a knowledge foundation and its development can enhance the professional development of social workers and their contribution to healthcare and patients.